2013
DOI: 10.1525/cond.2013.120107
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Factors for Stable Isotopes of Carbon and Nitrogen in Blood and Feathers from Chicks and Juveniles of the California Condor

Abstract: Abstract. Stable-isotope ratios of carbon ( 13 C/ 12 C; δ 13 C) and nitrogen ( 15 N/ 14 N; δ 15 N) in animal tissues are analyzed to estimate animal foraging ecology because these ratios reflect those of an animal's diet. This reflection is generally indirect, as stable-isotope ratios change with trophic level. These differences, called discrimination factors (reported as Δ), vary considerably by species and tissue. Variations in discrimination factors used in stableisotope mixing models can lead to inaccurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
(41 reference statements)
3
22
1
Order By: Relevance
“…Plasma was enriched in 15 N (but not in 13 C) when compared to RBC (Figure ). This plasma‐RBC difference is in agreement with the values calculated in captive birds feeding on isotopically controlled diets (Federer, Hollmen, Esler, Wooller, & Wang, ; Hahn, Hoye, Korthals, & Klaassen, ; Kurle et al., ). The δ 15 N differences arise from tissue‐specific isotopic discrimination factors due primarily to tissue‐specific protein, and hence amino acid, composition (Wolf, Carleton, & Martinez del Rio, ).…”
Section: Discussionsupporting
confidence: 88%
“…Plasma was enriched in 15 N (but not in 13 C) when compared to RBC (Figure ). This plasma‐RBC difference is in agreement with the values calculated in captive birds feeding on isotopically controlled diets (Federer, Hollmen, Esler, Wooller, & Wang, ; Hahn, Hoye, Korthals, & Klaassen, ; Kurle et al., ). The δ 15 N differences arise from tissue‐specific isotopic discrimination factors due primarily to tissue‐specific protein, and hence amino acid, composition (Wolf, Carleton, & Martinez del Rio, ).…”
Section: Discussionsupporting
confidence: 88%
“…that are similar to what we describe for toenails in dunlins. Studies in king Aptenodytes patagonicus and rockhopper Eudyptes chrysocome penguins (Cherel et al, 2005) and in California condors Gymnogyps californianus (Kurle et al, 2013) have also reported higher discrimination values in feathers than in blood, although not as high as we found in dunlin toenails. On the other hand, no difference was observed in Japanese quails Coturnix japonica and ring-billed gulls Larus delawarensis (Hobson and Clark, 1992b).…”
Section: Sample Typecontrasting
confidence: 52%
“…We used trophic enrichment factors of 3·1‰ ± 0·1 for δ 15 N and 0·4‰ ± 0·4‰ for δ 13 C observed for Californian condors on a controlled feeding trial (Kurle et al . ). We evaluated the mixing space qualitatively (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…We identified four isotopically distinct and biologically meaningful prey groups: large livestock (cows), small livestock (goat), camelids (vicuñas and guanacos) and marine mammals. We used trophic enrichment factors of 3Á1& AE 0Á1 for d 15 N and 0Á4& AE 0Á4& for d 13 C observed for Californian condors on a controlled feeding trial (Kurle et al 2013). We evaluated the mixing space qualitatively ( Fig.…”
Section: S T a B L E I S O T O P E A N A L Y S I Smentioning
confidence: 99%